간농양에 의해 이차적으로 발생하였다고 생각되는 안면부 농양 - 이재욱(Jae-Wook Lee); 김진욱(Jin-Wook Kim); 이상한(Sang-Han Lee) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2009)
In oral & maxillofacial surgery, careful management is necessary to avoid infection for old aged person or patient with diabetes mellitus(DM). We experienced a 69 years old female patient with DM, who has liver abscess and appendicitis, caused by Klebsiella pneumoniae, was developed into left mid-facial abscess and peritonitis. We report this case along with review of article for we have gained fairly good results in our attempt to resolve the patient’s abscess by means of I & D of the left mid-face and percutaneous catheter drainage of the stomach, supplemented with fluid and antibiotic therapy. KCI Citation Count: 0